Appointment scheduling system for car wash service - Lee, Ying Foong (2021)
This project is a mobile application for appointment scheduling system for car wash service. The demand of car wash service nowadays is increasing as most of the people are too busy to wash car themselves. Car wash center has provided various car wash or car detailing services such as foam wash, waxing, polishing which cause convenient to customers. However, there are some limitations found which customers has to queue up for a long time until their turn. During the peak hour, customers might have to wait for a few hours which actually waste customers’ time. Next, customers who are not familiar to the area are difficult to get a car wash service. They do not know which is the nearest car wash center from their own location. Another problem faced is the attendance of car wash appointment which people think that booking an appointment is troublesome as they have to go to the car wash center to book appointment or they have to make calls to discuss with staff for available time slot. These issues and limitations need to solved to improve the performance of appointment scheduling service. Hence, the proposed solutions in this application are able to solve the problems by integrating appointment scheduling system in car wash service mobile application. Customers are able to make appointment by using the application. Besides, GPS location tracking is used in order to solve the problem that users wanted to get car wash service at car wash center nearby them. The location of the car wash center is stored in the database and it will be retrieve and display at Google Map when it is nearby user’s current location. In addition, Improved Least Laxity First scheduling algorithm is also used to schedule the appointment on real-time basis. Customers can manage their appointment at anytime and anywhere. These proposed solutions are to improve the performance and customers’ user experience of the application.